Virtual airtime purchase in Nigeria: consumer attitude, behaviour and continuous usage - Okofu, Sebastina Nkechi (My University, 2021)
The Internet and mobile technologies have continued to transform the human, social and commercial engagements without the boundaries of space and time. These technologies are shaping every facet of human life, including socialisation, communication, and commerce. In Africa, the increase in mobile phone penetration is enhancing participation in the digital economy, with mobile commerce adoption being an important part. While there is growth in number by the players in the digital ecosystem in Africa, there are challenges with the adoption of such technologies. This thesis seeks to investigate the nuances of adoption of one such technology in the e-commerce space. This study, therefore, orients itself towards identifying factors slowing and/or promoting virtual airtime purchase, intention and continuous use. To achieve this, the study adopted an integrated theoretical approach using different aspects -the TAM, UTAUT, DOI and ECT. Quantitative data were collected from Delta State of Nigeria, using a sample of 390 participants to test the study’s integrated model. A product indicator structural equation modelling using the partial least square approach (Smart-PLS3) yielded some useful findings that help the study to make a significant contribution to literature and practice. The findings show that technological, social and contextual factors (at the personal level) are fundamental to promoting virtual airtime adoption of the mobile commerce technology. The findings also show a significant direct relationship between independent variable and dependent variables and also indicate usage satisfaction as a strong moderator for actual-continuous use relationship. The study is one of the first to have adopted an integrated framework to explain the end-to-end nuances of mobile commerce adoption in Africa’s largest country and economy. The study makes a significant contribution to theory and empirical work in emerging African economies in terms of mobile commerce adoption. It also offers practical recommendations to aid policy at the governmental level and both strategic and operational recommendations for telecommunication and players in the mobile commerce ecosystem
A thesis submitted to the School of Business Sciences, Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, in fulfilment of the requirement for the degree of Doctor of Philosophy (in Marketing Department), 2021